Pengembangan Modul Praktikum Biologi Berbantuan Video Praktikum Pada Materi Sel di Kelas XI - Oktavia, Nadira; Fajar, Najmiatul; Helmita, Roza; Delfita, Rina (Edusainstika: Jurnal Pembelajaran MIPA, 2024)
This research is motivated by the limited learning media such as PPT, videos, textbooks, and LKPD used which can hinder learning and the absence of a practical module or practical implementation guidelines that can hinder the course of the practical work and the lack of student motivation in learning biology. Therefore, the researcher developed a Video-Assisted Biology Practical Module on Cell material. With the aim of seeing the validity and practicality of the Video-Assisted Biology Practical Module on Cell Material which is valid and practical. The type of research used is development research (Research & Development). The RnD model used is 4-D. With reporting covering up to the third stage, namely develop which involves validity and practicality. The research instruments used are validity sheets and practicality sheets. The results of the study showed that the developed module met all aspects of development research and was in accordance with the desired module characteristics. The Video-Assisted Biology Practical Module was considered very valid with an average validation result reaching 92% for the module and 89% for the practical video. In addition, the average practicality result of the student response questionnaire is 87%, which is also categorized as very practical. Based on the response questionnaire from students, this practical module is included in the very practical category and is ready to be used in the learning process.